PROSPECTIVITY AND UNSPECIFICATION DISTANCE EDUCATION - Khodanych, Yurii Mykhailovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article deals with the possibilities and threats of distance learning, issues of its prospects and hopelessness. Author gives his own understanding of the educational process. On this basis appropriate conclusions are drawn.